The Influence of Organizational Culture and Digital Competence on Employee Performance Mediates Digital Transformation in English Language Education Institutions in Malang City - Abbadi Said Thalib; Fetty Poerwita Sary; Edi Witjara (Jurnal Syntax Transformation, 2024)
From the existing phenomenon, with so many course institutions in Malang and in order to continue to exist as the choice of English course seekers in Malang, it is necessary for all institutions to have good service performance for consumers. Likewise for teachers at the English course institution. A teacher also has demands on their performance in improving learning activities along with the times, including today, when technological advances are increasingly utilized by society as a whole. From the explanation of the phenomenon, it directly explains if there is an influence of culture and competence on the performance of a person, including educators or in an educational institution through digital transformation that occurs. In an institution or organization certainly has a culture that is formed and also the competence skills of organizational members that affect their performance as members of educators. In this era of digital transformation, educators are highly required to be able to adapt to the influence of digital technology developments that affect their performance in providing material. The purpose of research can be exploratory or descriptive or causal, these three properties of study depend on the stage at which knowledge of the topic under study increases. In this study, researchers used causal studies where one variable caused the other variable to change or not. In causal studies it is used to explain one or more factors that cause problems (Sekaran &; Bougie, 2017). The characteristics of respondents in this study were based on age, gender, and length of work. The characteristics of these respondents were identified based on questionnaires collected, namely in accordance with the sample in this study, namely 113 in English Language Education Institutions in Malang City, including English First (EF), Intensive English Course (IEC), Mayantara School and Malang International School (MIS).